2017
DOI: 10.1186/s13287-016-0444-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of human adipose derived stem cells in scleroderma in comparison to sex and age matched normal controls: implications for regenerative medicine

Abstract: BackgroundAdipose-derived stem cells (ADSCs) are emerging as an alternative stem cell source for cell-based therapies. Recent data suggest that autologous ADSC-enriched micrografting improves the effects of facial involvement in systemic sclerosis (SSc). We have extensively characterised ADSCs from SSc patients and compared their phenotype and function to healthy age- and sex-matched control ADSCs.MethodsADSCs were isolated and characterised from a cohort of six SSc patients (ADSC-SSc) and were compared to six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Some previous studies focused on the characteristics of SSc-MSCs for their possible therapeutic use for treating patients suffering from the most severe forms of SSc ( 13 ). However, to our knowledge, this is the first study evaluating the functional capacity of heterologous MSCs obtained from non-SSc donors when exposed to the oxidative environment encountered in patients, namely SSc serum.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies focused on the characteristics of SSc-MSCs for their possible therapeutic use for treating patients suffering from the most severe forms of SSc ( 13 ). However, to our knowledge, this is the first study evaluating the functional capacity of heterologous MSCs obtained from non-SSc donors when exposed to the oxidative environment encountered in patients, namely SSc serum.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, contradictory results are available about the properties of ASCs isolated from patients affected by autoimmune and chronic inflammatory diseases. For example, some reports demonstrated that ASCs from patients affected by systemic sclerosis show the same phenotypical and functional characteristics of their healthy counterparts (Scuderi et al, 2013;Capelli et al, 2017;Velier et al, 2019), while Griffin et al (2017) observed that ASCs from sclerodermic patients showed identical phenotype and differentiation capacity of those from healthy donors, but displayed reduced proliferation and migration capacity. Whilst, the presence of cardiovascular risk factors in cardiac patients seems to reduce ASC pluripotency and self-renewal, thus discouraging their autologous use in the clinical setting (Dimmeler and Leri, 2008;Krawiec et al, 2016).…”
Section: The Road Ahead In Immunomodulatory Potential Of Ascsmentioning
confidence: 99%
“…The inner thigh region was not statistically compared to the outer thigh and abdomen regions due to the relatively small sample size. from scleroderma, an autoimmune connective tissue disease, showed a lower proliferation rate and lower migration capacity than in the control ADSCs from healthy donors [37].…”
Section: Group Of Cellsmentioning
confidence: 86%